Community development through Islamic microfinance approach: The experience of Daarut Tauhid Peduli Bandung, Indonesia - Ela Nurhayati; Agus Ahmad Safei; Aya Ono (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2020)
The fields of zakat-based microfinance and community development are not often placed under the same theoretical lens that both aim to empower disadvantaged people. This study investigates the experiences of borrowers in the implementation of zakat-based microfinance and analyses the different driving factors they applied in their choice of the zakat-based microfinance of Daarut Tauhid Peduli in Bandung, Indonesia. It applies a community development framework, based on the five characteristics, to explore this Islamic microfinance approach as an effective community development program, which has a religious dimension. Primary data were obtained from semi-structured interviews with the borrowers along with participant observation at a weekly majelis meeting, and these were triangulated with information cross-checked with the management staff of the institution. The findings demonstrate three out of five characteristics of the zakat-based microfinance approach as an effective community development program. They include characteristics in constantly maintaining power relations between borrowers and the institution, increasing capability and ability of borrowers to be more independent and empowered, and long-term duration of the program and sustainability. The findings showed that spiritual factors appear to have been an additional driving force on top of economic and non-economic factors for most borrowers choosing this particular program.